Living Lab for People in Nandi County for Low-emission Food Systems - Kibet, Walter; Habermann, Birgit; Kachilei, Levy (International Livestock Research Institute, 2024)
We define a Living Lab for People (LL4P) as a space for citizens to co-design, test, demonstrate, and advance socio-technical innovations and associated modes of governance. It is an inclusive platform for citizens, government, civil society, companies, research organizations, to facilitate co-creation, rapid prototyping, or validation. One desirable feature is that the LL4P is physically embedded in an existing organizational structure with an interest in adopting the LL4P as their own in-house innovation cluster or ‘participatory incubator’. In Nandi County, the Kaimosi Agricultural Training Centre (ATC) has been selected as host for the LL4P